Sensitive capillary electrophoretic determination of mercury species with amperometric detection at a copper electrode after cation exchange preconcentration - Kubán, Petr; Houserová, Pavlína; Kubán, Pavel; Hauser, Peter C; Kubán, Vlastimil (Journal of separation science, 2007)
A capillary electrophoretic method for the separation of four mercury species with amperometric detection was developed. Inorganic Hg2+, methyl-, ethyl-, and phenyl-mercury were complexed with L-cysteine and separated in a counterelectroosmotic mode in an electrolyte solution comprised of 20 mM sodium tetraborate at pH 9.5. Amperometric detection of separated species was achieved at passivated copper electrode under electrocatalytic oxidation conditions. The four mercury species were separated in less than 8 min with LODs ranging from 170 to 450 microg/L. Cation exchange preconcentration was used to decrease the LODs down to 1.7 microg/L.
Keywords: Sensitivity and Specificity; elektrody; senzitivita a specificita; kationty; Time Factors; Electrodes; časové faktory; měď; Mercury; Electrochemistry; elektroforéza kapilární; iontová výměna; Cations; Microfluidic Analytical Techniques; elektrochemie; mikrofluidní analytické techniky; Copper; Electrophoresis, Capillary; Ion Exchange; rtuť